If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2600 = (2x + -6) * m + (x + 3) * m Reorder the terms: 2600 = (-6 + 2x) * m + (x + 3) * m Reorder the terms for easier multiplication: 2600 = m(-6 + 2x) + (x + 3) * m 2600 = (-6 * m + 2x * m) + (x + 3) * m 2600 = (-6m + 2mx) + (x + 3) * m Reorder the terms: 2600 = -6m + 2mx + (3 + x) * m Reorder the terms for easier multiplication: 2600 = -6m + 2mx + m(3 + x) 2600 = -6m + 2mx + (3 * m + x * m) 2600 = -6m + 2mx + (3m + mx) Reorder the terms: 2600 = -6m + 3m + 2mx + mx Combine like terms: -6m + 3m = -3m 2600 = -3m + 2mx + mx Combine like terms: 2mx + mx = 3mx 2600 = -3m + 3mx Solving 2600 = -3m + 3mx Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3m' to each side of the equation. 2600 + 3m = -3m + 3m + 3mx Combine like terms: -3m + 3m = 0 2600 + 3m = 0 + 3mx 2600 + 3m = 3mx Add '-3mx' to each side of the equation. 2600 + 3m + -3mx = 3mx + -3mx Combine like terms: 3mx + -3mx = 0 2600 + 3m + -3mx = 0 Add '-2600' to each side of the equation. 2600 + 3m + -2600 + -3mx = 0 + -2600 Reorder the terms: 2600 + -2600 + 3m + -3mx = 0 + -2600 Combine like terms: 2600 + -2600 = 0 0 + 3m + -3mx = 0 + -2600 3m + -3mx = 0 + -2600 Combine like terms: 0 + -2600 = -2600 3m + -3mx = -2600 Reorder the terms: 2600 + 3m + -3mx = -2600 + 2600 Combine like terms: -2600 + 2600 = 0 2600 + 3m + -3mx = 0 The solution to this equation could not be determined.
| 4x+5=16x+8-12x-3 | | 1.8x+2.8=2.5*2.1 | | -108=3(4+8n) | | 2[4x+1]+5=19 | | (8x-12)(5x-25)=0 | | (a)3.43x=5.6 | | 2[4x+1]5=19 | | 7(y-3)=4y-33 | | 25=3+9x | | 2+.142x=9 | | 3b-2=14 | | 2a-7=4(3a+1)-2 | | -6x-x+10=16-7x-5 | | 3x-5(x-5)=-7+4x-16 | | (-3)(-2)+(-2)(4)= | | 12+5x=-2x-11 | | 13=1-7x-5x | | X^2-15x-1000=0 | | (7y+x)=4 | | y=3x^3+27x^2 | | 8(x+4)=7(2x+3) | | 5(x-4)-3(x-2)=12 | | 2a-17=21 | | 0.22(x+9)=0.2x+3.6 | | =(2x)(3x+1) | | -2w+8-2w=-w-7w+3w | | 0=(2x)(3x+1) | | 39.95+.35m=69.70 | | 2x+3x=2x-4 | | -8-(12-16)= | | 7a-(3a-4)=16 | | (-3)(2)(-1)(-3)= |